2010
DOI: 10.3758/brm.42.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizer 1.0: A varying-coefficient meta-analytic tool

Abstract: Around the turn of the 20th century, communicable infectious diseases were a great threat to human populations. It was only with the advent of vaccination protocols that many of such modern "plagues" were successfully controlled-indeed, today's children are routinely vaccinated against diseases such as measles and smallpox. Karl Pearson, one of the fathers of modern statistics, lived during this period. Given the controversies that existed at the time, he too was interested in the efficacy of newly developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Significant results are implicated if the 95% CI of the differences did not include zero. 69 Results showed that CAPE-pos (95% CI = −.018, −.054) and CAPE-neg (95% CI = .054, .096) scores appeared to be more internally reliable in younger samples. Age group of samples did not make a difference to internal reliability for full scale CAPE-42 and CAPEdep scores.…”
Section: Psychometric Properties Of Capementioning
confidence: 86%
See 1 more Smart Citation
“…Significant results are implicated if the 95% CI of the differences did not include zero. 69 Results showed that CAPE-pos (95% CI = −.018, −.054) and CAPE-neg (95% CI = .054, .096) scores appeared to be more internally reliable in younger samples. Age group of samples did not make a difference to internal reliability for full scale CAPE-42 and CAPEdep scores.…”
Section: Psychometric Properties Of Capementioning
confidence: 86%
“…A meta-analysis of original reliability coefficients using a varying-coefficient model of aggregation computation was performed in Excel 2007 using the meta-analytic tool Synthesizer 1.0. [68][69][70] The level of original alpha values reported for CAPE-42 (n = 5) had a meta-analytic mean of 0.91 (SD = 0.05), while that of CAPE-pos (n = 9) had a meta-analytic mean of 0.84 (SD = 0.1). Alpha values of …”
Section: Reliability Generalizationmentioning
confidence: 99%
“…For the present analysis, we used the varying-coefficient model 2 recommended by Bonett (2008, 2009, 2010) and Krizan (2010) because (1) it does not rely on the unrealistic assumptions made by other fixed effects meta-analytic models (e.g., the existence of a single population effect size), (2) Bonett (2008, 2009, 2010) has demonstrated that varying-coefficient models provide more precise confidence intervals than other models, and (3) it performs well in the presence of correlation heterogeneity and non-randomly selected studies (Bonett, 2008; c.f. Brannick et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Brannick et al, 2011). Synthesizer 1.0 (Krizan, 2010) was used for computing point estimates and 95% confidence intervals (95% CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we follow the recommendation that confidence intervals be constructed around unweighted averages (Shuster, 2010), which tend to outperform confidence intervals generated based on traditional fixed-effect or even random-effects models (Bonett, 2009(Bonett, , 2010. ploys an unweighted estimate of the cumulative effect size (see Bonett, 2009;Krizan, 2010, for more detail).…”
Section: (N -1)mentioning
confidence: 99%